FHEIs draft regulations, 2023: Concerns and contradictions - Bhushan, Sudhanshu (Economic and Political Weekly)
For the last two decades, there have been attempts to allow the branch campuses of foreign universities through legislative measures. However, in the recent Draft UGC Regulations, 2023, effort is made to allow such universities to operate and confer degree, bypassing even the legislative route. The article contends the point that the draft regulation is anti-constitutional and stands on weak legal grounds. It will distort the public higher education institutions and by creating further exclusion, it fails to serve the national interests. The policymakers need to deliberate further on the implications of such a policy on the already unequal landscape of education.- Reproduced